Histological and cytological studies on the developing thymus of sharpsnout seabream, Diplodus puntazzo - ROMANO, NICLA (1999)

(untitled)
The structure of the developing thymus of the marine teleost, Diplodus puntazzo, was studied by light and transmission electron microscopy. The first anlage of the thymus developed by d 20 postfertilisation (p.f.) as a group of undifferentiated cells dorsal to the epithelium of the branchial chamber. The organ increased significantly in size around d 51–66 p.f. and differentiation of cortex and medulla occurred concomitantly. On the basis of their localisation, 4 main types of epithelial cell were distinguished: (1) limiting, adjacent to the connective capsule; (2) medullary and cortical reticular cells; (3) nurse cells, located in the corticomedullary boundary; (4) Hassall-like corpuscles. The majority of medium to large blast-like lymphoid cells were localised in the medulla, while small lymphocytes were housed in the cortical region. These morphological features were maintained at later stages. However, in juveniles in the medulla we observed reticular epithelial cells with cysts and rare Hassall-like corpuscles. The study was designed to obtain more information concerning the histology of the developing thymus of sharpsnout seabream and give a concise description of the differentiation of epithelial cells and lymphoid cells in the thymic parenchyma.